ANALISIS SEMIOTIKA POS STRUKTURAL PADA FOTO RHEIN II (A POST-STRUCTURAL SEMIOTICS ANALYSIS OF THE PHOTOGRAPH RHEIN II) - Markus Jiuhanteng; Acep Iwan Saidi; R. Drajatno Widi Utomo (Universitas Trisakti, 2021)
Abstract This paper is a study of Andreas Gursky’s photo Rhein II. In this study, the post-structural semiotic analysis method is used to interpret meaning based on signs on the Rhein II. The post-structural semiotic analysis becomes the basis for interpreting meanings using related references. In the study of Rhein II photo objects, visual text analysis is expected to provide positive benefits for the development of photography, especially academically. Rhein II is a photo by Andreas Gursky. In Rhein II’s photograph, a contemporary photo is presented as a multi-reality representation analyzed using the post-structural semiotic method. The object of research is interpreted as a text that has a layer of meaning that is squeezed out of its essence by semiotics. The deconstruction of the signification system in the visual element is identified by reading the structural postal semiotic theory codes: text analysis process, creation process. The results of semiotic extraction produce an interpretive study of Rhein II which is full of meaning.Keyword: imagery, photography, semioticaAbstrak Makalah ini merupakan kajian dari foto Rhein II karya Andreas Gursky. Dalam kajian ini digunakan metode analisis semiotika post struktural untuk menginterpretasikan makna berdasarkan tanda-tanda pada Rhein. Analisis semiotika post struktural menjadi landasan dalam menginterpretasikan makna-makna dengan menggunakan referensi terkait. analisis teks visual, dalam kajian objek foto Rhein II diharapkan dapat memberikan kebermanfaatan yang positif bagi perkembangan fotografi khususnya secara akademis. Rhein II adalah foto karya Andreas Gursky. Dalam karya Rhein II, sebuah foto kontemporer dihadirkan sebagai representasi multi realitas yang dianalisis menggunakan metode semiotika post struktural. Objek penelitian dimaknai sebagai teks yang memiliki lapisan makna yang terperas esensinya oleh semiotika. Dekonstruksi sistem penandaan dalam elemen visual diidentifikasikan dengan pembacaan kode-kode teori semiotika pos struktural. Proses analisis teks, proses penciptaan. Hasil ekstraksi semiotika menghasilkan kajian interpretatif Rhein II yang sarat makna.Kata kunci: citra imaji, fotografi, semiotika